Analysis of Learning Concentration in Science Learning of Grade V Students of Purwoyoso 01 Elementary School - Riangga Maharani; Bagas Kurnianto (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to analyze the level of learning concentration, identify influencing factors, examine the relationship between learning concentration and learning outcomes, and explore teachers' efforts to address students' concentration difficulties among fifth-grade students at Purwoyoso 01 State Elementary School in Semarang City. The research used a qualitative descriptive approach with a saturated sampling technique, involving all 27 fifth-grade students as research subjects. Data were collected through interviews, observations, and documentation over three days, dividing students into three groups to obtain in-depth information. Data analysis employed the Miles and Huberman model, including data reduction, display, and conclusion drawing. The results showed that students' learning concentration levels were generally in the moderate category, averaging 70.33%. 37.04% of students were categorized as having high concentration, 37.04% moderate concentration, and 25.93% low concentration. Factors influencing learning concentration included physical health, learning environment, learning style, and motivation. Students with higher learning concentration tended to achieve better learning outcomes. Teachers' efforts to overcome concentration difficulties included using various learning methods, strengthening motivation, and creating a conducive learning environment.